Effects of nitrate and phosphate availabilities on growth, photosynthesis and pigment and protein contents in colour strains of Hypnea musciformis (Wulfen in Jacqu.) J.V. Lamour. (Gigartinales, Rhodophyta) - Martins, Aline P.; Necchi Junior, Orlando [UNESP]; Colepicolo, Pio; Yokoya, Nair S. (Sociedade Brasileira de Farmacognosia, 2011)
In Brazil, Hypnea musciformis is the main raw material for carrageenan production and the knowledge of nitrogen and phosphorus metabolism in algae is critical for the success of cultivation because these elements can limit seaweed productivity. Thus, the objective of this study was to evaluate the effects of nitrate (zero to 100 μM) and nitrate plus phosphate (zero to 25 μM) availabilities on the growth, the contents of photosynthetic pigments (phycobiliproteins and chlorophyll a) and proteins, and the photosynthesis and respiration of the brown (BR) and light green (LG) strains of H. musciformis. The results revealed metabolic differences between the colour strains of H. musciformis for nitrogen metabolism: upon nitrate addition, the LG strain stored nitrogen mainly as proteins, while the BR strain stored it as proteins and pigments. Moreover, the respiration of the LG strain and the photosynthesis of the BR strain increased with nitrate concentrations, indicating that the BR strain fixed more photosynthetic carbon than the LG strain.
Keywords: colour strain; Hypnea; nitrate; phosphate; Photosynthesis